Optimalisasi Tenaga Kerja pada PT X - Devi Marcella Kahar (Jurnal Titra, 2020)
PT X is a company that produce galvalum, roofs, gutters, etc. The problem of the company is the number of SPKs that are canceled because orders have not been reached or met the target. This research was accomplished to optimize the work force at PT X. The method used in the study is the Worker and Machine Process Chart and Gang Process Chart. The charts are used to observe the operator’s idle time. The result showed there were many operators who were idle because of a simple production process so that the operators could be allocated to other machines or rearranged the number of operators in each machine. The addition of sensors equipment to the barbed wire machine can reduce the number of barbed wire operators so that 1 operator can handle 2 machines. Reducing the number of operators on several machines shows an increase in the productive percentage of operators. There is also a reduction in the number of operators in the initial conditions and the proposed conditions so that the remaining time can be used for the production of rejected requests.